Postur kerja dengan keluhan musculoskeletal disorders pada penjahit rumahan (industry rumah tangga) - Ridhila, Istikhomah; Darnoto, Sri (Holistik Jurnal Kesehatan, 2023)
Background: The Occupational Health and Safety (OHS) problems of informal workers do not have health insurance, they are not officially registered, and compensation for work accidents is not available. The activities and attitudes of workers towards tools and ways of working have great potential in causing health problems and diseases. These health problems can occur in a short or long time. Musculoskeletal complaints are one of the health problems caused by work factors.Purpose: To analyse the relationship between work posture and musculoskeletal complaints in home industry tailors.Method: The research design used is quantitative method, with cross sectional research type using observation. This study was conducted by measuring at the same time between the dependent variable and the independent variable to determine the work attitude that affects the occurrence of musculoskeletal complaints in tailor workers. This study took 16 villages in Nguter sub-district. The population in this study were all Home Industry tailor workers in Nguter District as many as 70 tailors. The sample used in this study were all home industry tailor workers in Nguter District, namely 70 people. The sampling technique is a way of taking a representative sample of the population.Results: Based on RULA analysis, it was found that there were 30 respondents who were at moderate risk level and 40 respondents at high risk in posture examination. This condition certainly requires special handling so as not to have a negative impact on tailors in the future. Based on the NBM analysis, it was found that there were 21 respondents who experienced musculoskeletal disorders MSDs complaints in the low category and 49 respondents who experienced MSDs complaints in the moderate category, so further treatment was not needed. Based on the results of the chi-square test, a p-value of 0.035 was obtained. This p-value is smaller than the significance level of 0.05, which means there is a significant relationship between work posture and MSDs complaints in Home Industry tailor workers in Nguter District.Conclusion: Based on the results of the chi-square test, it can be concluded that work posture has a significant influence on MSDs complaints in tailor workers in Nguter District.Keywords: Home Industry Tailors; Musculoskeletal Disorders; Working postures.Pendahuluan: Masalah Kesehatan dan Keselamatan Kerja (K3) pekerja informal tidak memiliki asuransi kesehatan, mereka tidak terdaftar secara resmi, serta tidak tersedianya santunan akibat kecelakaan kerja. Aktivitas dan sikap tubuh para pekerja terhadap alat dan cara kerja memiliki potensi besar dalam menimbulkan gangguan kesehatan hingga penyakit. Gangguan kesehatan tersebut dapat terjadi dalam waktu yang singkat maupun lama. Keluhan musculoskeletal merupakan salah satu gangguan kesehatan yang diakibatkan oleh faktor pekerjaan.Tujuan: Untuk menganalisis hubungan postur kerja dengan keluhan muskuloskeletal pada penjahit home industry.Metode: Rancangan penelitian yang digunakan adalah metode kuantitatif, dengan jenis penelitian cross sectional menggunakan observasi. Penelitian ini dilakukan dengan mengukur pada waktu yang bersamaan antara variable terikat dan variable bebas untuk mengetahui sikap kerja yang mempengaruhi terjadinya keluhan musculoskeletal pada pekerja penjahit. Penelitian ini mengambil 16 Kelurahan di Kecamatan Nguter. Populasi pada penelitian ini adalah seluruh pekerja penjahit rumahan di Kecamatan Nguter sebanyak 70 orang penjahit. Sampel yang digunakan pada penelitian ini adalah seluruh pekerja penjahit home industry di Kecamatan Nguter yaitu sebanyak 70 orang. Teknik pengambilan sampel merupakan cara mengambil sampel yang representative dari populasi.Hasil: Berdasarkan analisis RULA diperoleh hasil bahwa terdapat 30 responden yang berada pada level risiko sedang dan 40 responden pada risiko tinggi dalam pemeriksaan postur tubuh. Kondisi ini tentu memerlukan adanya penanganan khusus supaya tidak memberikan dampak negative bagi para penjahit di masa yang akan datang. Berdasarkan analisis NBM didapatkan hasil bahwa terdapat 21 responden yang mengalami keluhan MSDs dengan kategori rendah dan 49 responden yang mengalami keluhan MSDs dengan kategori sedang, sehingga belum diperlukan penanganan lebih lanjut. Berdasarkan hasil uji chi-square, diperoleh nilai p (p-value) sebesar 0,035. p-value ini lebih kecil dari tingkat signifikansi 0,05, yang berarti ada hubungan yang signifikan antara postur kerja dengan keluhan MSDs pada pekerja penjahit rumahan di Kecamatan Nguter.Simpulan: Postur kerja memiliki pengaruh yang signifikan terhadap keluhan MSDs pada pekerja penjahit di Kecamatan Nguter.